Editing of a specific strain of escherichia coli in the mouse gut using native phages - Li, Ping (2023)
There is a lack of methodological investigation of the in situ functions of bacterial species in microecosystems. Here, we used native phages as a microbial editing tool for eliminating Escherichia coli strain MG1655 labeled with green fluorescent protein (GFP) in the mouse gut. The virulent phages (W1 and W3) possessed host specificity at both the genus and species levels, resulting in an 8.8-log10 difference in the titer of viable bacteria after 12 h of phage treatment compared with that in the phage-free control in an in vitro test. In vivo, they reduced strain MG1655 colonizing the mouse gut at concentrations of 106 to 108 CFU g-1 to a 102 CFU g-1 level, which is almost undetectable by the plate colony-counting method. Moreover, the impact of phage treatment on the microbial community structure of the mouse gut was not significant (P > 0.05), indicating that native phages can effectively edit a target bacterium, with limited perturbation of microbial diversity and relative abundance. Therefore, we developed an engineering technique for investigation of the functions of a specific bacterium by depleting its abundance in microecosystems. IMPORTANCE This report describes a gut engineering technique for investigation of the functions of a specific bacterium. Native phages with host specificity can knock down the corresponding E. coli strain in the mouse gut with limited perturbation of microbial diversity and relative abundance, indicating that they, as a microbial editing tool, can effectively edit the abundance of a target bacterium. Such an approach is undoubtedly of interest in the context of lack of knowledge of how to methodologically study the in situ function of a specific species in a complex microecosystem.